Current Treatment Of Obstetric Brachial Plexus Injury: A Review Article - Muhammad Al Faatih; Tito Sumarwoto (Syntax Corporation Indonesia, 2024)
Obstetric brachial plexus injury (OBPI) is a peripheral nervous system disorder. The incidence of OBPI dropped 47.1% over the sixteen-year study period, from 1.7 to 0.9 cases per 1000 live births. In Indonesia, the incidence of OBPI is 0.141%. Even though most babies recover spontaneously in the first 3 months of life, 20-30% suffer permanent functional deficits, which significantly impair their quality of life, which means a small number remain with bad recovery which requires surgical brachial plexus exploration. For children with complex medical conditions, it is important to implement and refer multidisciplinary strategies as early as possible. This can greatly improve their chances of functional recovery. To provide the best possible care, primary care physicians, physiatrists, nerve surgeons, and occupational and physical therapists should work together and modify current treatment paradigms. This will help to ensure improved quality care for these children. Successful treatment of patients with OBPI begins with an accurate understanding of the anatomy of the brachial plexus and the pathophysiology of nerve injury. Two main treatments/therapies for OBPI were identified: conservative treatment and surgical treatment. This review will explain the latest update on the management and rehabilitation of OBPI